Semantic and Structural Relationships between French Emotive Phrases (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article we analyzed the semantic and structural relationships between phrasemes expressing human emotions in French. In addition, we have cited the factors that can influence these relationships. We gave examples and presented the particularities of language used to express these feelings.